Does pain vary across the menstrual cycle? A review. (21st April 2015) - Iacovides, S.; Avidon, I.; Baker, F.C.
Abstract Reproductive hormones are implicated in moderating pain. Animal studies support both pronociceptive and antinociceptive actions of oestradiol and progesterone suggesting that the net effect of these hormones on pain is complex and likely depends on the interaction between hormones and the extent of fluctuation rather than absolute hormone levels. Several clinical pain conditions show variation in symptom severity across the menstrual cycle. Though, there is still no consensus on whether the menstrual cycle influences experimental pain sensitivity in healthy individuals. Comprehensive literature searches on clinical and experimental pain across the menstrual cycle, as well as gonadal hormones and pain were performed using the electronic databases PubMed, Google Scholar and the Cochrane Library. Full‐text manuscripts were reviewed for relevancy and reference lists were cross‐checked for additional relevant studies. Most of the more recent, well‐controlled studies show that menstrual cycle phase has no effect on the perception of pain in healthy, pain‐free women. Although recent studies investigating pain‐related brain activation have shown differential activation patterns across the menstrual cycle in regions involved with cognitive and motor function, even in the absence of a behavioural pain response, suggesting that cognitive pain and bodily awareness systems are sensitive to menstrual cycle phase. The interaction between the gonadal hormones and pain perception is intricate and not entirely understood. We suggest further investigations on the association between female reproductive hormones and pain sensitivity by exploring the interaction between clinical and experimental pain and the hormone changes that characterize puberty, post‐partum and the menopause transition.